Relationships of Fruit Production and Regional Development in the Northern Great Plain Region - Harsányi, Zsolt Gergely; Harsányi, Endre; Nagy, János Attila (Acta Agraria Debreceniensis, 2005)
The role of retaining population in agriculture is stronger and more significant in the long run in the North Great Plain Region compared to other regions. The region has a significant processing industry along with a good basis for producing raw materials, developed food processing capicity and high quality agricultural products typical of the region. The GDP in agriculture, forestry and game management is somewhat higher than the national average.Variety is of cardinal importance when establishing the quality of horticultural products and determining the product value. The Hungarian breeding results of apple, quince, apricot, cherry, raspberry, red and black currant are promising.The regulation system of EU the vegetable and fruit market is based on Retail Cooperatives Producers. With the establishment of national vegetable- and fruit production and retail organizations, the market regulation, production and quality development issues of the sector can be handled and solved. Reaching EU standards in fruit production can only be achieved with up-to-date plantation systems and breed selection. A key issue in development is establishing the required financial resources for investments and updating production. In order to reach these standards, significant state subsidies and good credit conditions are needed. By solving these tasks, the sector is expected to become self-financed without government help.The pursuit of safer production, improving quality and increasing yields require the establishment of up-to-date irrigation systems. The improvement of family farms, motivating land concentration is necessary for increasing average size of plants. Establishing the above mentioned conditions is important since the vegetable-fruit sector is of great significance in the employment of rurally based population, improving their living conditions and executing rural development programs.